Racial differences in primary central nervous system lymphoma incidence and survival rates - Pulido, Jose S. (Duke University Press, 2009)
To determine racial and ethnic differences in incidence and survival in patients with primary central nervous system lymphoma (PCNSL), NCI Surveillance, Epidemiology, and End Results (SEER) program data from 1992 to 2002 were queried. Data were substratified by age (20–49 years vs. 50 or above) and race (White, Black, Asian/Pacific Islander [A/PI], American Indian/Alaskan Native [AI/AN]). Incidence of PCNSL and survival were calculated by SEER*Stat software. The incidence rates were 0.94 per 100,000 per year (95% confidence interval [CI] 0.90–0.98) for Whites, 1.10 (95% CI 0.98–1.22) for Blacks, 0.51 (95% CI 0.28–0.74) for AI/AN, and 0.64 (95% CI 0.56–0.72) for A/PI. In patients aged 20–49 years the rates were 0.72 (95% CI 0.68–0.76) for Whites, 1.43 (95% CI 1.27–1.59) for Blacks, 0.58 (95% CI 0.30–0.86) for AI/AN, and 0.21 (CI 0.15–0.27) for A/PI. In patients over 49 years, the rates were 1.30 (95% CI 1.22–1.38) for Whites, 0.56 (95% CI 0.40–0.72) for Blacks, 0.34 (95% CI 0–0.70) for AI/AN, and 1.31 (95% CI 1.00–1.53) for A/PI. PCNSL incidence for ages 20–49 years for Black patients was twice that for Whites. Incidence for ages over 49 years for Whites was twice that for Blacks. Survival at 12 months, 24 months, and 60 months was higher among Whites than Blacks. Research is needed to determine the origin of these differences.